Ocular Fatigue Syndrome and academic stress in nursing students during confinement due to COVID-19 - Huyhua Gutiérrez, Sonia Celedonia; Meléndez Tuesta, Jessica; Odar Rojas, Cintya Elisabeth; Ruiz Cruz, Dalila; Tejada Muñoz, Sonia (Journal of the University of Zulia, 2021)
Objective: To determine the relationship of Computer Visual Syndrome with academic stress in nursing students during confinement by COVID-19. Methods: descriptive, relational, cross-sectional study; whose non-probabilistic sample was 119 nursing students from Amazonas, Peru; The survey technique was used and two instruments were applied through the Google form, the 16-item Computer Vision Syndrome Questionnaire (CVS-Q), (sensitivity and specificity is greater than 70%) and the SISCO SV academic stress questionnaire of 47 items (Aiken V concordance coefficient greater than 0.75), during the months of November to December 2020. The data were processed in the Statistical Package for the Social Sciences program version 25, from which the descriptive statistics were obtained and the nonparametric Chi Square statistical test. Conclusions: Visual Computer Syndrome is not significantly related to academic stress in nursing students during confinement by COVID-19. However, it is necessary to implement improvement measures in the teaching-learning process by increasing asynchronous hours.